Penggunaan Aplikasi Edukasi Seksual dalam Mendukung Sustainable Development Goals 2030: Usage of Sexual Education Applications for Sustainable Development Goals, 2030 - Dhani Wijaya; Humaira Ramzi; Azian Firman Saputra; Ilmiyatul Muhimmah (Jurnal Sains dan Kesehatan, 2023)
Increasing sexual reproductive health information and knowledge about Human Immunodeficiency Virus/ Acquired Immune Deficiency Syndrome in adolescents is one of the targets of the Sustainable Development Goals, 2030. The use of sexual education applications helps educate adolescents that supports the achievement of these targets. This study describes the effect of sexual health education applications on adolescent knowledge and decreases the prevalence of Human Immunodeficiency Virus/ Acquired Immune Deficiency Syndrome to support the 2030 Sustainable Development Goals. This research is a literature study of articles published in NCBI, Google Scholar, and PubMed. The keywords used in the article search were: sex education, android application, Human Immunodeficiency Virus/ Acquired Immune Deficiency Syndrome, and reproduction health. Inclusion criteria were articles published in 2016-2020, using English or Indonesian, original article, can be accessed in full text, free of charge and the manuscript content’s were relevant to the study. Review articles and duplicate journals were excluded. In this study, only ten of the 1250 articles met the inclusion criteria. Study shows that sexual education applications can increase adolescents' understanding of reproductive health, good and healthy sexuality, improve sexual attitudes and behavior, and also reduce the prevalence of Human Immunodeficiency Virus/ Acquired Immune Deficiency Syndrome that supports the 2030 Sustainable Development Goals. Keywords: Sexual Education Applications, Reproductive Health, HIV/AIDS Abstrak Peningkatan informasi kesehatan reproduksi dan seksual serta pengetahuan mengenai Human Immunodeficiency Virus dan Acquired Immune Deficiency Syndrome pada remaja merupakan salah satu target Sustainable Development Goals 2030. Penggunaan aplikasi edukasi seksual membantu edukasi terkait kesehatan seksual dan reproduksi yang mendukung pencapaian target tersebut. Tujuan penelitian ini untuk mendeskripsikan pengaruh aplikasi edukasi kesehatan seksual terhadap pengetahuan remaja dan penurunan prevalensi Human Immunodeficiency Virus/ Acquired Immune Deficiency Syndrome dalam kaitannya untuk mendukung Sustainable Development Goals 2030. Penelitian ini merupakan studi literatur atas artikel yang terbit NCBI, Google Scholar dan PubMed. Kata kunci yang digunakan dalam pencarian artikel adalah: sex education, application android, Human Immunodeficiency Virus/ Acquired Immune Deficiency Syndrome dan reproduction health. Kriteria inklusi meliputi artikel terbitan 2016-2020, berbahasa Inggris atau Indonesia, original article, dapat diakses secara lengkap, gratis dan isi naskah relevan dengan topik penelitian. Review article dan duplikasi jurnal dikeluarkan dari penelitian. Dalam penelitian ini, sepuluh dari 1250 artikel yang memenuhi kriteria inklusi. Berdasarkan tinjauan artikel diketahui bahwa aplikasi edukasi seksual dapat meningkatkan pemahaman remaja terkait kesehatan reproduksi, seksualitas yang sehat, memperbaiki sikap dan perilaku seksual serta menurunkan prevalensi Human Immunodeficiency Virus/ Acquired Immune Deficiency Syndrome. Hal ini mendukung tercapainya Sustainable Development Goals 2030. Kata Kunci: Aplikasi Edukasi Seksual, Kesehatan Reproduksi, HIV/AIDS